Unilateral termination of employment by the company Reviewed from the Principle of Job Protection - Laila Rizqillah; Amanda Putri Fajrin; Shafa Zhafira Khalid; Aqtika Deeba Lubis (ISNU Nine-Star Multidisciplinary Journal, 2026)
Unilateral termination of employment (PHK) by companies is a crucial problem in industrial relations because it has the potential to cause injustice and violations of workers' rights. The practice of unilateral layoffs is often carried out without going through the procedures set by laws and regulations, thus contradicting the principle of protecting workers as parties who are structurally in a weak position. This study aims to analyze the practice of unilateral layoffs by companies from the principles of worker protection and the labor law framework in Indonesia. The research method used is normative legal research with a legislative and conceptual approach, through analysis of the Manpower Law, the Job Creation Law, and related implementing regulations. The results of the study show that the principle of worker protection emphasizes the guarantee of job security, fair treatment, and legal protection of workers' normative rights, including the right to severance pay and dispute resolution mechanisms. Unilateral layoffs that are carried out without a valid reason and without proper legal procedures are a form of violation of this principle. Therefore, consistent law enforcement and strengthening the role of labor supervision are needed to prevent unilateral layoffs and ensure effective protection of workers' rights.